2021
DOI: 10.3389/fonc.2020.539592
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Positive Surgical Margins in Patients With Prostate Cancer After Radical Prostatectomy: A Systematic Review and Meta-Analysis

Abstract: Background and ObjectivesPrevious studies have demonstrated that positive surgical margins (PSMs) were independent predictive factors for biochemical and oncologic outcomes in patients with prostate cancer (PCa). This study aimed to conduct a meta-analysis to identify the predictive factors for PSMs after radical prostatectomy (RP).MethodsWe selected eligible studies via the electronic databases, such as PubMed, Web of Science, and EMBASE, from inception to December 2020. The risk factors for PSMs following RP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
(22 reference statements)
1
13
0
Order By: Relevance
“…For high-risk patients, who can choose to retain one side or not to retain the neurovascular bundle during surgery, or to combine ADT before surgery to reduce the rate of PSMs. Previous studies have shown that several clinical and pathologic factors have the potential of predicting PSMs ( 4 , 8 , 23 ). Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For high-risk patients, who can choose to retain one side or not to retain the neurovascular bundle during surgery, or to combine ADT before surgery to reduce the rate of PSMs. Previous studies have shown that several clinical and pathologic factors have the potential of predicting PSMs ( 4 , 8 , 23 ). Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al. ( 8 ) conducted a comprehensive meta-analysis and systematic review with a sample of 50,014 patients, and showed that TPSA, biopsy-based Gleason score, postoperative Gleason score, pTNM, positive lymph nodes, extra-prostatic extension, and seminal vesicle invasion are independent prognostic factors for PSMs. None of the studies, however, have systematically predicted the post-LRP margin status based on mpMRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, in a recent publication from the same group, the authors attempted to use the following strategy as a combination of both multi-parametric magnetic resonance imaging and prostate health index to predict the EPE, 18 based on the strong correlation between EPE and PSM (at least a four-fold increase in PSM). 15 However, the current Dr. Yang’s study also failed to investigate this part, and in fact, even though they have studied the aforementioned factor (EPE), many reported important and independent risk factors were not included in both studies, 13,18 contributing to the absence of any response to why partial NS RARP was associated with PSM in their study.…”
mentioning
confidence: 88%
“…Factors that predict non focal positive MOR are the number of positive cores in preoperative biopsy, stage pT3a and pT3b [ 24 ]. In contrast, Zhang et al conducted a comprehensive meta-analysis and systematic review with high diversity and a sample of 50,014 patients, and showed that age, BMI, prostate volume and type of surgical technique are not reliable and independent prognostic factors for margin positivity [ 43 ]. They confirmed, however, that preoperative PSA levels, Gleason score at the initial diagnostic biopsy, Gleason score and stage at the prostatectomy specimen, and presence of positive lymph nodes, extraprostatic extension and seminal vesicle invasion are associated with positive MOR [ 43 ].…”
Section: Factors Affecting the Probability Of Margin Positivitymentioning
confidence: 99%